Cover Picture: Scalable Coating of Single‐Source Nickel Hexadecanethiolate Precursor on 3D Graphitic Petals for Asymmetric Supercapacitors (Energy Technol. 5/2017). Issue 5 (3rd May 2017) - Gupta, Ritu; Fisher, Timothy S.
Abstract : Scalable Coating of 3D Graphene Architectures : The cover image illustrates the schematic of roll‐to‐roll printing of nickel hexadecanethiolate ink that can be decomposed under ambient condition to yield NiO x S y as a pseudocapacitive layer. The nickel‐based pseudocapacitive layer is conformally coated onto three‐dimensional graphitic structures to increase the surface area and enhance the capacitance. An optimized loading of the pseudocapacitive layer onto three‐dimensional graphene petals yields a supercapacitor with high specific capacitance (≈2360 F g −1 ) and stability over 5000 cycles. More details can be found in the Full Paper by Ritu Gupta and Timothy Fisher of Indian Institute of Technology‐Jodhpur and Purdue University, USA onpage 740 in Issue 5, 2017 (DOI:10.1002/ente.201600475 ).